Comparing peri-urban versus rural poverty and child malnutrition reduction: Insights from Southeast Asia - Thi Hoa Pahlisch; Priyanka Parvathi; Hermann Waibel (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2017)
Success in reducing monetary poverty in Southeast Asia does not fully translate into reduction in malnutrition. Using a three-year panel data from one province each in Thailand, Lao PDR and Vietnam, we study the correlation between monetary poverty and nutritional outcomes of children under five. Furthermore, we analyze differences between nutrition outcomes of children between rural and peri-urban areas. We apply ordinary least squares, two stage least squares and quantile regression models and find that nutrition remains a problem despite achievements in poverty alleviation. Results also show significant differences across countries as well as between peri-urban and rural areas.
Keywords: I15; I30; R11; 330; Poverty; Child malnutrition; Peri-urban; Rural; Southeast Asia